Analisis Determinan Agresivitas Pajak Pada Perusahaan Sektor Industri - Sabna, Zona Atasa Azizah; Wulandari, Sartika (Akuntansi dan Manajemen, 2021)
This research aimed to analyze the factors affecting tax aggressiveness. The variables used were leverage, intensity of inventory, intensity of fixed asset, profitability, and liquidity. The approach used was quantitative with secondary data sources obtained from annual financial reports on the Indonesia Stock Exchange (IDX). The population of this research were 53 manufacturing industry companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2020 period using the purposive sampling method. Based on the purposive sampling method, 84 samples were obtained from 21 manufacturing industry companies listed on the IDX for the 2017-2020 period. The data analysis technique in this research used panel data with the Eviews Program as a tool. The results obtained indicated that the factors affecting tax aggressiveness were the variable intensity of fixed assets and profitability. This research states that the intensity of fixed assets has a negative and significant effect on tax aggressiveness, while profitability has a positive and significant effect on tax aggressiveness. Meanwhile, the factors that have no effect on tax aggressiveness are the variables of leverage, intensity of inventory, and liquidity.